THE EFFECT OF NaOH CONCENTRATION IN DELIGNIFICATION PROCESS ON MICROCRYSTALLINE CELLULOSE FROM GREEN ALGAE (Cladophora sp.) AS THE RENEWABLE MARINE PRODUCT - I Gusti Ngurah Jemmy Anton Prasetia; Shelia Deviana; Trisna Damayanti; Angga Cahyadi; I Made Agus Gelgel Wirasuta (Sanata Dharma University, 2018)
Research on marine natural resources as an excipient material of pharmaceutical product is still rare. One of the marine products is the green algae, Cladophora sp. High cellulose content causes Cladophora sp. which can be used as an alternative material of microcrystalline cellulose (SM). There are two stages to produce SM, namely delignification and hydrolysis. Delignification is the process of removing the lignin of complex compounds. The delignification process is carried out chemically in alkaline situation using a NaOH solution which dissolves lignin, carbohydrates, organic acids, and resins so that cellulose is released from its bonds. This is important because the presence of lignin may inhibit acid penetration prior to hydrolysis. Therefore, the purpose of this study is to investigate the effect of delignification by using NaOH solution at various concentrations (2, 4, and 6%) to cellulose content and physical character of microcrystalline cellulose from Cladophora sp. (SMC). In the hydrolysis process, 5% HCl solution was used. SMCs of various concentrations of NaOH were observed and the cellulose levels included alpha, beta and gamma levels. While the physical character observation is done on Scanning Electron Microscopy (SEM) test. Based on the cellulose content, the higher the concentration of NaOH used, the higher the alpha cellulose will increase. The opposite result occurs on the measurement of beta and gamma cellulose. Based on SEM test, it appears that there is no effect of increasing NaOH concentration on physical character of SMC.